Macroprudential rules and monetary policy when financial frictions matter - Jeannine Bailliu; Césaire Meh; Yahong Zhang (Bank of Canada, 2012)
This paper examines the interaction between monetary policy and macroprudential policy and whether policy makers should respond to financial imbalances. To address this issue, we build a dynamic general equilibrium model that features financial market frictions and financial shocks as well as standard macroeconomic shocks. We estimate the model using Canadian data. Based on these estimates, we show that it is beneficial to react to financial imbalances. The size of these benefits depends on the nature of the shock where the benefits are larger in the presence of financial shocks that have broader effects on the macroeconomy.
Keywords: E42; E50; E60; 330; Monetary policy framework; Financial stability; Financial markets; Economic models